Missing inferior vena cava: report of a rare case - Perumal, Senthil Kumar; Subramaniam, Sugi R. V. (International Surgery Journal, 2019)
Missing inferior vena cava (IVC) is an uncommon but well recognised anomaly. Our case was a 32 year old male, presented to us with features suggestive of gastric outlet obstruction. When evaluated he was found to have gastric outlet obstruction secondary to cicatrized duodenum and a large subcutaneous vein running from supra pubic region towards the left axilla. Further imaging revealed the complete absence of inferior vena cava and the large collateral drainng the venous blood from lower half of the body into left interal jugular vein. Surgical correction of this rare anomaly is not required in the absence of deep vein thrombosis and venous ulcers of lower extremity. Here we report a case of young male with incidentally detected missing IVC as a contribution to the limited literature available on this rare anomaly.